Rodzaj gramatyczny rzeczownika jako nośnik informacji pozagramatycznej I. Przegląd literatury dotyczącej rodzaju gramatycznego - Koziarski, Mirosław; Krysiak, Adrian P. (Investigationes Linguisticae, 2012)
This article aims at investigating the nature of the gender system in Polish. The paper includes a review of various approaches to the problem, as seen by psycholinguistics, neurolinguistics and feminist linguistics, as well as an attempt at presenting a synchronic view on the gender system. It is also the theoretical introduction to a following empirical article treating of Polish genders.